The Role of Public Perception in Shaping Urban Development Policies - Ardiansyah, Herman (Generasi Sains Indonesia, 2024)
This qualitative study examines how the salience of public perception has an impact on the establishment of urban development policies. Using semi-structured interviews with local residents and municipal decision-makers, the study explores the way of how change in urban planning projects and activities is based on the changing public opinion. The results are that the two key mechanisms that emanate out of civic engagement are the delivery of feedback and the reinforcement of accountability and responsiveness, both of which are valuable in influencing the outcome of policy. The most prominent factors include socio-economic status, personal interest in the issues of cities, and trust in the leadership. These studies also outline the views of the policymakers in the eyes of the population, and, thus, prove that community involvement can be used to trigger the changes within any urban project. This research, therefore, fills theoretical and methodological gaps identified before by illuminating the intricacies of involvement of people and the resulting effects on policy reform in an urban context. The findings highlight the fact that the promotional culture of collaboration under action plans targeting urban development is more effective and leads to social trust. On this basis, it is suggested that future studies should continue with the investigation of the perception of the population at different stages of development and explore the use of online social media as an enabling tool of increasing civic engagement in the policy making process.